Differences In Cadmium (Cd) Levels In The Blood of Active Smokers And Passive Smokers With Type 2 Diabetic In Puskesmas Kedungdoro Surabaya - Christ Kartika Rahayuningsih; Devi Puspitasari; Ayu Puspitasari (Jurnal Teknokes, 2022)
The degree of smoking habits in the urban community is still high, although carried out health promotion of harmful substances in cigarettes, one of which is cadmium (Cd). The dangers of cadmium in cigarette smoke causes harm to active and passive smokers. Increased exposure of cigarettes will lead to an increase in the burden of disease in groups at risk such as people with Diabetic Type 2 (DMT2). The purpose of this study was to determine the differences in levels of cadmium (Cd) in the blood of active smokers and passive smokers patients with DMT2 in Puskesmas Kedungdoro Surabaya. The type of this research is a comparative with cross-sectional study design conducted in the Toxicology Laboratory of the Department of Health Analyst and Research and Standardization Center of Industry in August 2020-May 2021. The independent variable in this study is active smokers and passive smokers patients with DMT2, and the dependent variable in this research is the content of cadmium (Cd) in the blood. Analysis of the levels of cadmium in the blood using Atomic Absorption Spectrophotometer by the method of acidifying carbon furnaces. The results showed range levels of cadmium in blood in 8 people suffer from Type 2 Diabetic as active smokers are 0.605-1.5535 µg/dL. While the range levels of cadmium in the blood of the 8 people who suffer from Type 2 Diabetic as passive smoking are 0.5648-2.7045 µg/dL. Based on the results of statistical tests using test Independent Sample T-Test, it can be concluded that there is no difference in the levels of cadmium (Cd) in active smokers and passive smokers patients with DMT2 in Puskesmas Kedungdoro Surabaya.